TEACHING ENGLISH THROUGH DIGITAL TOOLS: ENHANCING LANGUAGE LEARNING IN THE DIGITAL AGE - MOYDINOVA, Elmira Kamariddinovna (The Lingua Spectrum, 2025)
This article explores the integration of digital tools in teaching English as a second language (ESL) and their impact on learner engagement, motivation, and language proficiency. With the rapid advancement of technology, digital tools such as mobile applications, interactive platforms, gamification, and multimedia resources have become increasingly prevalent in ESL education. Employing a mixed-method approach combining quantitative surveys, proficiency tests, and qualitative classroom observations, this research investigates the effectiveness and challenges of using digital tools in diverse ESL learning environments. Findings indicate that digital tools significantly improve learner outcomes by fostering interactive, personalized, and autonomous learning experiences. However, barriers including digital literacy gaps, unequal access to technology, and the need for teacher training persist. The study highlights practical implications for educators and policymakers to optimize the use of digital tools in English language teaching.